PENGEMBANGAN STUDENT’S WORKSHEET BERBASIS CTL MENGGUNAKAN SAKEM - M Amir (STKIP Muhammadiyah Muara Bungo, 2019)
This research is a developmental research that aimed to produce CTL-based Students' Worksheets using SAKEM (Waste Packaging) in Class X High School Descriptive Text material. The instruments in this study were material and design / media assessment sheets, teacher assessment questionnaires and participant response questionnaires. The study was conducted at SMAN 11 Tebo. Product validation is carried out by material experts, design / media experts. Product testing is done by means of individual trials and small group trials. The results of the study indicated that Students' Worksheets are feasible for use by teachers and students. This can be proven by the validity and practicality of Students' Worksheets. The Students' validity Worksheets could be seen from the results of the validation of material and design / media experts with the category